PENERAPAN ANJURAN MEDIATOR DALAM MENYELESAIKAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Atmanegara, Fadhoil Rafsanjani; Wahyudi, Eko (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research is based on the author's awareness of the vital role of industrial relations in the development of legal science, which is marked by every business step, government policy, ratification of laws and regulations related to industrial relations, which has a direct impact on the wider community and influences the micro economy as well as the macro economy. Therefore, this research aims to provide the latest exact material within the scope of law based on empirical matters. Considering the purpose of the existence of industrial relations, which is one of the constitutional mandates and the guaranteed rights of citizens, especially in the economic sector, both from the entrepreneur's side and from the workforce side, it is necessary to have definite legal instruments and the best policies are those that feel they are just or at least have certainty. law. Legal certainty will be achieved if the mediator can decide the case or present a solution to make peace in order to avoid the litigation process as conceptualized in the legal instrument for industrial relations disputes. The research was carried out using empirical juridical methods with a combination of data through the process of collecting data from sources and legal sources such as previous research, teaching materials and others. The existence of written recommendations is often seen as lacking compelling legal force due to the nature of law which is a tool of sosial control or as a medium that can be used by those in power to be enforced politically. This research will cover the fact that the mediator's written recommendations still do not contain legal certainty for the parties after carrying out tripartite mediation negotiations even though the aim of holding tripartite negotiations is so that the case does not reach the litigation stage.